PENGARUH KETIDAKADILAN ORGANISASI TERHADAP PERILAKU KERJA KONTRAPRODUKTIF PADA PEKERJA MILENIAL DI INDONESIA: PENGARUH KETIDAKADILAN ORGANISASI TERHADAP PERILAKU KERJA KONTRAPRODUKTIF PADA PEKERJA MILENIAL DI INDONESIA - Putri, Reinisa Afrida; Wulandari, Jeni; Aprilia, Hani Damayanti (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
This study aims aims to determine the effects of person-organization fit and employeerelations on counterproductive work behavior among millennial employees in Indonesia. Thisresearch uses the quantitative approach with explanatory research type. The sample in thisstudy were millennial employees in Indonesia who had taken counterproductive workbehavior as many as 385 respondents, which was carried out using non-probability samplingtechnique. Data were obtained from questionnaires distributed online using Likert scale.Data processing in this study used descriptive analysis and simple linear regression. Theresults of this study indicate that there is an influence of organizational injustice oncounterproductive work behavior of millennial workers in Indonesia and there is also asimultaneous influence of organizational injustice on counterproductive work behavior ofmillennial workers in Indonesia.